The Relationship Between Islamic Work Ethics and Organizational Commitment - Al Kilani, Haytham S. D. (2010)
This study investigates the relationship between Islamic work ethics and organizational commitment. In this study, Islamic work ethics was treated as independent variables. organizational commitment as a dependent variable. A questionnaire survey of 63 employees working in Jawwal Telecommunication Company in Palestine. The reliability analysis show that the Cronbach's Alpha value for all the variables under study were satisfactorily acceptable except for normative commitment (.542). Due to a very low reliability for normative commitment, the item was removed from the study and was not considered for futher analysis. The descriptive analysis of the variables especially the mean value for Islamic Work Ethics, affective commitment and continuance commitment (where the responses were tapped on the 5 point likert scale) were all above moderate and towards agreement. However, the results from correlation analysis show no significant relations between Islamic Work Ethics and Organizational Commitment.